Recurrence after skin-sparing mastectomy and immediate transverse rectus abdominis musculocutaneous flap reconstruction for invasive breast cancer - Liang, Tsung-Jung (BioMed Central, 2013)
BACKGROUND: The aim of this study was to evaluate the recurrence pattern after skin-sparing mastectomy (SSM) and immediate breast reconstruction (IBR) using transverse rectus abdominis musculocutaneous (TRAM) flap in patients with invasive breast cancer. METHODS: From 1995 to 2010, patients with invasive breast cancer who underwent SSM followed by IBR using TRAM flap were retrospectively reviewed. The pattern of the first recurrence event was recorded. RESULTS: We identified 249 consecutive patients with invasive breast cancer, two-thirds of whom (67.1%) were diagnosed with stage II or stage III disease. During a median follow-up period of 53 months, three (1.2%) local, 13 (5.2%) regional, 34 (13.7%) distant, and five (2.0%) concurrent locoregional and distant recurrences were observed. The median time to recurrences was 26 months (range, 2 to 70 months) for all recurrences, 23 months (range, 2 to 64 months) for locoregional recurrences, and 26 months (range, 8 to 70 months) for distant recurrences. All local recurrent lesions were detectable by careful physical examination, and detection of local recurrence suggested the presence of distant metastasis (60.0%). In contrast to distant metastasis, the risk of locoregional recurrence did not increase significantly with an increase in disease stage. The 5-year overall, locoregional relapse-free, and distant relapse-free survival rates were 89.7%, 90.8%, and 81.6%, respectively. CONCLUSIONS: SSM followed by immediate reconstruction using TRAM flap is an oncologically safe procedure even in patients with advanced-stage disease. Detection of local recurrence is crucial and can be aided by a thorough physical examination.